If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-2x + 10) = 42 Reorder the terms: 7(10 + -2x) = 42 (10 * 7 + -2x * 7) = 42 (70 + -14x) = 42 Solving 70 + -14x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-70' to each side of the equation. 70 + -70 + -14x = 42 + -70 Combine like terms: 70 + -70 = 0 0 + -14x = 42 + -70 -14x = 42 + -70 Combine like terms: 42 + -70 = -28 -14x = -28 Divide each side by '-14'. x = 2 Simplifying x = 2
| 8(2-5x)=-264 | | 11.3+-7.2=3.82 | | 747-60x=0 | | 4y+5(5+y)=-2 | | ax+by=0 | | 2(-4r+2)=-6(-8+2r) | | .53y+2.5=5.1 | | -88+9z=z | | 3xz+4-8=1 | | 2(4d+5h)-(9h-5d)= | | 2x+1+4x+4=4 | | 7u-22=-1 | | -8(6x+5)=-520 | | 4h+7=4h | | x+3=30 | | 220+0.15x=368.50 | | (3x^2y+7xy^2)(x^2y^3-2y^2)= | | 11=1+8m+2n | | -5x-10=2-(x-4) | | 3(2+e)-4e=e+16 | | 9.1x+23.1=-4.2 | | (5x^5y^4)(2x^5y)= | | 21b=-19 | | 7(4x-2)=322 | | 112=4x+6(x+7) | | 5x-5=33 | | 6(6m-6)=-8(-4m+5) | | -3b-3+9b=-5b-4+11b | | x+5y=-14 | | 3x-10(x+2)=13-17x | | -6y=72 | | 7x-3x=5x+13 |